Constructing A Climate-Smart Readiness Index for smallholder farmers: The case of prioritized Bundles of Climate Information Services and Climate Smart Agriculture in Ghana - Damba, Osman Tahidu (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Bundling of CSA-CIS are relatively distinct although they are impactful when integrated. Farmers and Agric Officers rated 21 innovations based on CSA, gender, youth and social inclusion (GSI), enabling environment (EE), one-health achievement (OHA), and end-user friendliness (EUF). for prioritization, bundling and to construct the Climate Smart Readiness Index (CSRI). There were fundamental differences in concordance in their respective rankings. A high level of concordance exist between ratings by farmers and advisors on the CS score; moderate concordance on OHA and a lower concordance on GSI. CS, GSI, OHA, EUF, and EE integrates towards CSRI through the Fornell-Larcker and the Heterotrait-Monotrait criteria. OHA was a key determinant of CSRI for farmers while EE was for Agric Officers.